2021
DOI: 10.3390/ani11020443
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation Effect of Oleuropein Extract Combined with Betaine, Magnesium, and Vitamin E on Pigs’ Performance and Meat Quality Characteristics

Abstract: This study evaluates the effect of the dietary combination of oleuropein extract (1200 mg/kg) and betaine (1000 mg/kg), magnesium oxide (600 mg/kg), and α–tocopheryl acetate (400 mg/kg), or a half-dose of these compounds, on pigs’ performance, oxidative status, and meat quality characteristics (drip loss, TBARS, and texture and fatty acid profile of intramuscular fat). Sixty-six barrows and females were slaughtered at 120 kg of BW. Performance and carcass yield were not changed by treatments. The high-dose mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…2 Chlorogenic acid-enriched extracts from many other natural plants have been used in livestock as potential feed additives to promote animal health, enhance antioxidative capacity and improve meat quality. [13][14][15][16][17] For instance, dietary supplementation with Lonicera macranthoides Hand.-Mazz.-derived chlorogenic acid has been reported to improve meat quality and muscle fiber characteristics of finishing pigs. 12 Up to now, to our knowledge no feeding experiments have examined the effects of dietary SRE supplementation in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Chlorogenic acid-enriched extracts from many other natural plants have been used in livestock as potential feed additives to promote animal health, enhance antioxidative capacity and improve meat quality. [13][14][15][16][17] For instance, dietary supplementation with Lonicera macranthoides Hand.-Mazz.-derived chlorogenic acid has been reported to improve meat quality and muscle fiber characteristics of finishing pigs. 12 Up to now, to our knowledge no feeding experiments have examined the effects of dietary SRE supplementation in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a huge amount of polyphenol‐enriched stevia residue is produced and abandoned by steviol glycoside manufactories 2 . Chlorogenic acid‐enriched extracts from many other natural plants have been used in livestock as potential feed additives to promote animal health, enhance antioxidative capacity and improve meat quality 13‐17 . For instance, dietary supplementation with Lonicera macranthoides Hand.‐Mazz.‐derived chlorogenic acid has been reported to improve meat quality and muscle fiber characteristics of finishing pigs 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the changes in the composition of fatty acids of the pork intramuscular fat induced by the immunobiotic TUA4408L-fermented okara feed were modest when compared with those induced by other dietary interventions [ 35 , 36 ]. Drastic changes in the composition of fatty acids of pork intramuscular fat are induced only with diets that aim for remarkable quantitative and/or qualitative changes in the source of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in addition to its nutritional value, the fatty acid composition also influences the oxidative stability of meat [ 37 ]. Recently, it was shown that an olive by-product combined with betaine, magnesium, and vitamin E is capable of modifying pigs’ performance and meat quality characteristics [ 35 ]. The researchers supplemented the basal conventional diet of pigs with the mix mentioned before (high-dose diet) or half-dose of each compound (low-dose diet).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation